2011
DOI: 10.1002/mus.21935
|View full text |Cite
|
Sign up to set email alerts
|

Single‐fiber conduction velocity test allows earlier detection of abnormalities in diabetes

Abstract: SF-CV is able to detect mild myelin damage with higher sensitivity than conventional tests. The use of SF-CV may be a helpful tool in the early identification of diabetic polyneuropathy, and it may be useful for tailoring an approach to diabetic polyneuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…We found significant changes in protein carbonylation and misfolding in diabetic mice which correlated well with reductions in sciatic NCV and myelin thickness and was in agreement with previous studies in dbdb mice [2] and human type II diabetes [3]. Sod1 −/− mice exhibited all of the physiological changes observed in dbdb mice (with the exception of myelin thickness) at 6 months of age and biochemical changes (elevation of protein carbonylation and alteration in protein surface hydrophobicity), however, the changes at this age were not as robust as that observed in 5-mo-old dbdb mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found significant changes in protein carbonylation and misfolding in diabetic mice which correlated well with reductions in sciatic NCV and myelin thickness and was in agreement with previous studies in dbdb mice [2] and human type II diabetes [3]. Sod1 −/− mice exhibited all of the physiological changes observed in dbdb mice (with the exception of myelin thickness) at 6 months of age and biochemical changes (elevation of protein carbonylation and alteration in protein surface hydrophobicity), however, the changes at this age were not as robust as that observed in 5-mo-old dbdb mice.…”
Section: Discussionsupporting
confidence: 92%
“…In humans, the pathologic changes include neuronal/Schwann cell dysfunction, axonal degeneration and chronic motor/sensory neuron demyelination [1]. Reduced nerve conduction velocity (NCV) is also observed in diabetic mice [2] and in human type II diabetics [3]. Considerable evidence exists to suggest that oxidative stress may play a critical role in reduction of sciatic nerve conduction and alteration of sciatic/myelin morphology and function in diabetes [4], [5], [6]; for example, rodent models of type I and II diabetes show increase in oxidative stress and/or damage, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, just as SF-CV studies have been demonstrated to be more sensitive than routine motor NCS, 2,3 we have demonstrated that SFF-wave studies are more sensitive than conventional F-wave recordings in the detection of early DPN. Our technique has the advantages of being able to assess the entire length of motor nerves, can be performed with a standard CN, and can detect segmental involvement that occurs in early DPN.…”
Section: Discussionmentioning
confidence: 53%
“…This technique has demonstrated an increased sensitivity over routine NCS for a range of neuropathy etiologies, 1 as well as both subclinical and clinical stages of diabetesrelated neuropathy. 2,3 Regarding routine NCS, prolonged F-wave latencies have been demonstrated to be the earliest and most sensitive measure to detect both subclinical and overt large-fiber neuropathy in diabetes. 4,5 We explored another electrophysiological technique that, in essence, combines SF-CV with F waves: singlefiber electromyography (SFEMG) recordings of F waves, or SFF waves.…”
Section: Accepted 1 July 2018mentioning
confidence: 99%
See 1 more Smart Citation